Influence of Job Crafting on Evidence-Based Practical Skills of Dental Hygienists - Min-ji Kim; Kyu-ri Kim; Yun-ji Kim; Seo-yeon Im; You-bin Cho; Ru-by Choi; Hee-jung Lim (The Korean Society of Dental Hygiene Science, 2023)
Background: As the medical knowledge base grows at an accelerating rate, evidence-based clinical performance becomes increasingly important for providing quality care. Previous studies have highlighted the need to promote job crafting to actualize evidence-based practical skills in the medical field. This study aimed to investigate the degree of evidence-based practice among dental hygienists and assess the impact of job crafting on the evidence-based practical skills of dental hygienists.Methods: Dental hygienists working at dental hospitals and clinics in Seoul and Gyeonggi Province were surveyed between February 28 and April 6, 2023. The sample was comprised of 267 participants. The hypotheses were tested independent t-tests, one-way analysis of variance, Pearson's correlation coefficients, and multiple regression analyses using SPSS 29.0. Results: The degree of job crafting by dental hygienists demonstrated significant differences based on educational attainment, workplace size, and workplace type. Evidence-based practical skills exhibited significant variations based on educational attainment and job position. All job crafting subfactors demonstrated positive correlations with evidence-based practical skills. The job crafting subfactors affecting the evidence-based practical skills of dental hygienists were 'increasing structural job resources' and 'increasing challenging job demands,' which together explained 38.7% of the variance in evidence-based practical skills. Conclusion: This study demonstrates that job crafting was positively and significantly correlated with evidence-based practical skills. To strengthen the job crafting ability of dental hygienists, improving environmental conditions and fostering an organizational culture that motivates continued participation in education is necessary. The development and promotion of programs that enable learning of the latest evidence should be actively pursued. Additionally, regular attendance at workshops and participation in organizational evidence-based practice education programs are necessary.